Total Quality Management in Higher Education - Masruroh Masruroh (Beginner: Journal of Teaching and Education Management, 2026)
Total Quality Management (TQM) is a planned system for managing higher education resources aimed at enhancing service quality effectively and efficiently, with a focus on continuous improvement and the satisfaction of stakeholders such as students, faculty, and the community. This article outlines the TQM concept—covering its definition, core principles (customer satisfaction, individual recognition, data-driven management, and continuous improvement via the PDCA cycle), and implementation elements such as top management commitment, adequate resources, a steering committee, structured planning, and supporting infrastructure. While the application of TQM in higher education faces challenges due to the qualitative nature of its output—namely graduates—it is effective in boosting competitiveness through process improvements, quality standards, organizational culture shifts, and strong customer relationships.